MECHANISMS OF MONITORING OF FINANCIAL AND ECONOMIC ACTIVITIES IN JOINT-STOCK COMPANIES WITH STATE PARTICIPATION - A. Yakovlev (Вестник университета, 2018)
The mechanisms of control in the sphere of corporate governance of joint-stock companies are considered. Due to the more complicated management and control system in state joint-stock companies in comparison with private companies, they are characterized by a much larger number of problems, one of which is the construction of an eective control system. Such monitoring mechanisms used in domestic corporate practice as: formation of an audit committee under the board of directors, the involvement of independent experts in audit committee, the formation of an internal control unit - are analyzed